The culture of war : literature of the siege of Paris 1870-1871 - Foss, Colin (Studies in modern and contemporary France ;, 2020)
"The Culture of War explores the unexpected flourishing of literature both high and low during the Siege of Paris at the end of the Franco-Prussian War, 1870-1871. When Prussian forces completely blockaded Paris, isolating the city from the outside world, Parisians turned to literature to resist the enemy, to fill the idle hours under siege, and to articulate their place in history. This cultural boom was a conscious effort on the part of literary institutions like newspapers, publishers, and theaters to ensure the viability of their industries during a period of political uncertainty. To do so, many publishers, editors, and directors sought legitimacy through populism, promoting literature written by anonymous and unknown authors or that spoke to populist ideas. A study of national tragedy on a local scale, The Culture of War goes beyond traditional narratives of communal or individual psychology, and studies institutional responses to financial and political instability, viewing literature as a product of economic and political forces."--